Sistem Informasi Layanana Data Pernikahan pada Kantor KUA Kecamatan Tinggi Raja Berbasis WebSistem Informasi Layanana Data Pernikahan pada Kantor KUA Kecamatan Tinggi Raja Berbasis Web - Nur Rizka Alya Putri Sinurat (SABER : Jurnal Teknik Informatika, Sains dan Ilmu Komunikasi, 2025)
The aim of this research is to design and build an online marriage registration service information system at the KUA Tinggi Raja District using the CodeIgniter framework which can support or facilitate marriage registration at the KUA Tinggi Raja District. The research method used in this research is a qualitative method with the waterfall system development method. The applications created are designed using Unified Modeling Language (UML) including Use Case Diagrams, Activity Diagrams, Sequence Diagrams, and Class Diagrams. The software used in designing this application uses the PHP programming language, XAMPP as the web server, MySQL as the database. The result of this search is an application for the Tinggi Raja Regency KUA Online Marriage Registration Service so that this application can support the Telluwanua Regency KUA Online Marriage Registration Service. The application was tested using the black box test method and results were obtained without program errors, while for questionnaire testing using usability the results were very in line with the score, namely utilization of 96%. Hopefully this application can help online marriage registration services at the KUA Tinggi Raja District.